(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
The Imperialist and Cambridge historiography on theMuslim Communal politics and partition of India and on the political changesamong the Muslims of colonial India tend to fall into five separatecategories. The historians of the firstcategory are of the opinion that the omissions, tactical errors and diplomaticblunders on the part of the Indian National Congress changed the Muslimpolitics and led to the growth of the Muslim Communal politics subsequentlyresulting in the form of the partition of India. The second category of thesehistorians are of the opinion that the forces of the colonial policy and theconstitutional measures adopted by the colonial state helped to the emergenceand growth of the Muslim communal politics and led to the partition ofIndia. It has been suggested by the third category of these scholars that the growth of the Muslim separatism in India was manipulated and determined by the Muslim elites at the national and provincial level whose propaganda based on communalidentification was responded to the Muslims of colonial India. The historiansof the fourth category have argued that although the colonial policy and itsevolution of the representative from of the government led to the emergence and consolidation of the Muslim communal politics but the demand of a separate Muslim state wasnot the design of Muslims of India. It has been viewed by the scholars of thefifth category that the Muslim separatism in colonial India and the partitionof India was the result of the interplay between the three major political playersi.e., the British, the Indian National Congress and the All India Muslim Leagueand that the partition of India was a first major act of decolonization.